2010
DOI: 10.1182/blood-2009-07-230631
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 increases B-cell IgG production in a feed-forward proinflammatory mechanism to skew hematopoiesis and elevate myeloid production

Abstract: Src homology 2 domain-containing inositol 5-phosphatase (SHIP ؊/؊ ) animals display an age-related increase in interleukin-6 (IL-6), a decrease in B lymphopoiesis, and an elevation in myelopoiesis. We investigated the origin of the IL-6 production and show that it is largely produced by peritoneal and splenic macrophages. IL-6 production by these macrophages is not a direct result of the loss of SHIP: IL-6 production is not spontaneous, is absent from bone marrow-derived macrophages, declines with prolonged cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 70 publications
6
81
0
Order By: Relevance
“…We also demonstrated that tumor cells are capable of stimulating such modified Th2 responses, featuring production of IL-10 and IL-4 and secretion of IgG4 by B cells. Also consistent with a tumor-associated inflammatory environment, VEGF, known to polarize Th2-biased cytokine production by PBMCs through induction of IL-10-secreting cells such as Tregs (53), along with well-described tumor-induced inflammatory mediators IL-6 and MCP-1 (53)(54)(55)(56), was found at significantly increased levels (P < 0.001; Supplemental Figure 3A Figure 8. n = 33.…”
Section: Discussionmentioning
confidence: 59%
“…We also demonstrated that tumor cells are capable of stimulating such modified Th2 responses, featuring production of IL-10 and IL-4 and secretion of IgG4 by B cells. Also consistent with a tumor-associated inflammatory environment, VEGF, known to polarize Th2-biased cytokine production by PBMCs through induction of IL-10-secreting cells such as Tregs (53), along with well-described tumor-induced inflammatory mediators IL-6 and MCP-1 (53)(54)(55)(56), was found at significantly increased levels (P < 0.001; Supplemental Figure 3A Figure 8. n = 33.…”
Section: Discussionmentioning
confidence: 59%
“…This finding was unexpected and now questions the true nature of the lung disease in SHIP-1 2/2 mice, and suggests that the M2 classification of this disorder is not strictly correct. IL-6 is elevated in serum and BAL of C57.SHIP-1 2/2 mice (6,8,10,31). It is well known to influence hematopoietic progenitor number and myelopoiesis: injection of IL-6 into mice can induce myelopoiesis and myeloproliferative disease (32), and IL-6 can synergize with other cytokines to drive production of immature hematopoietic progenitors (33,34 (20,(37)(38)(39)(40)(41)(42), and there is evidence that the 129 strain is autoimmune prone (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…SHIP-1 2/2 mice show an increase in circulating IL-6, which is thought to suppress lymphopoiesis and promote myelopoiesis (5,6). Recently, macrophages and dendritic cells from SHIP-1 2/2 mice have been implicated as the IL-6-overproducing cells (7,8). At a young age, SHIP-1 2/2 mice develop an inflammatory lung disease accompanied by M2 macrophage polarization reflected in chitinase crystal accumulation in alveolar macrophages and in lungs (3,4,9,10).…”
mentioning
confidence: 99%
“…However IL-6 is not directly associated with the immunoinhibitory activity UC-MSC on CD4 + T cell [39]. IL-6 was originally isolated and cloned as a B-cell differentiation factor that induced terminal B-cell differentiation and supported the production of immunoglobulin G (IgG) [40,41] We observed that although the level of IL-6 was higher in coculture system, the neutralizing antibodies to IL-6 did not affect the immunomodulation on B cells. In conclusion, we presumed that IL-6 does not participate in the immunoinhibitory activity of UC-MSC on B cells.…”
Section: Discussionmentioning
confidence: 99%